2019
DOI: 10.1021/acsami.8b18525
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinductivity of Porous Biphasic Calcium Phosphate Ceramic Spheres with Nanocrystalline and Their Efficacy in Guiding Bone Regeneration

Abstract: Conventional biphasic calcium phosphate (BCP) bioceramics are facing many challenges to meet the demands of regenerative medicine, and their biological properties are limited to a large extent due to the large grain size in comparison with nanocrystalline of natural bone mineral. Herein, this study aimed to fabricate porous BCP ceramic spheres with nanocrystalline (BCP-N) by combining alginate gelatinizing with microwave hybrid sintering methods and investigated their in vitro and in vivo combinational osteoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 55 publications
2
64
0
1
Order By: Relevance
“…11,28,35 Our previous studies have certified that compared to the conventional ones with micro-scale surface structure, BCP ceramics with nanocrystalline can promote osteogenic differentiation of BMSCs in vitro, and improve osteoinductivity and bone regeneration in vivo. 7 In the present study, SEM images (Figure 1) showed that CaO addition could markedly inhibit the grain growth in BCP ceramics, as the grain size of BCP ceramics gradually decreased with the increase of CaO amount from 1% to 4%. When the content of CaO increased up to 3%, the average grain sizes of the obtained BCP ceramics (<270 nm) F I G U R E 7 The expression of osteogenic genes (ie Runx-2, Osx, Alp, Ocn, and Opn) in BMSCs cultured on the four kinds of BCP ceramics.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…11,28,35 Our previous studies have certified that compared to the conventional ones with micro-scale surface structure, BCP ceramics with nanocrystalline can promote osteogenic differentiation of BMSCs in vitro, and improve osteoinductivity and bone regeneration in vivo. 7 In the present study, SEM images (Figure 1) showed that CaO addition could markedly inhibit the grain growth in BCP ceramics, as the grain size of BCP ceramics gradually decreased with the increase of CaO amount from 1% to 4%. When the content of CaO increased up to 3%, the average grain sizes of the obtained BCP ceramics (<270 nm) F I G U R E 7 The expression of osteogenic genes (ie Runx-2, Osx, Alp, Ocn, and Opn) in BMSCs cultured on the four kinds of BCP ceramics.…”
Section: Discussionsupporting
confidence: 54%
“…Cell proliferation was quantified by AlamarBlue method as mentioned before. 7 BMSCs attached on the samples were also stained with TRITC-conjugated-phalloidin (1:200, Sigma) for cytoskeletal protein (F-actin), and DAPI (1:200, Sigma) for cell nuclei, and then the staining was examined under a confocal laser scanning microscopy (CLSM, TCS SP5, Leica, Germany). The morphology of BMSCs was also observed by SEM following the procedures as described before.…”
Section: Cell Spreading and Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroxyapatite, tricalcium phosphate, amorphous calcium phosphate, and biphasic calcium phosphate have inorganic composition and crystal structure similar to those of natural bones, so they are the most commonly used bioceramics in orthopedic surgery. In recent years, with the research and development of tissue engineering, porous CPCs, as a kind of bone tissue engineering cell scaffolds, have been widely used in the repair and replacement of bone defects [112]. At present, many methods of preparing porous ceramics have been developed, such as organic foam impregnation method, foaming method, and adding pore-forming agent ( Figure 15).…”
Section: Bioceramicsmentioning
confidence: 99%